2018
DOI: 10.21273/hortsci12738-17
|View full text |Cite
|
Sign up to set email alerts
|

Potato Response to Polyhalite as a Potassium Source Fertilizer in Brazil: Yield and Quality

Abstract: Polyhalite (PH) is a hydrated sulfate evaporite mineral containing potassium, calcium, magnesium, and sulfur, nutrients all required in significant quantities by crops, but has limited evaluation as a fertilizer for potato (Solanum tuberosum L.). Fertilizer source and application rate field trials were conducted to evaluate PH as a fertilizer for potato production in the weathered tropical soils in Brazil. We selected two locations in the potato producing region of Southeast … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 24 publications
2
25
0
Order By: Relevance
“…3). The absence of an effect of different K fertilizer application timings (preplanting and prehilling) on the specific gravity of tubers has also been reported in the literature (Kumar et al, 2007, Mohr andTomasiewicz, 2012;Noor et al, 2012;Mello et al, 2018). On the other hand, the specific gravity of potato tubers commonly decreases with the application of KCl, either in the planting furrows (Mohr and Tomasiewicz, 2012;Silva and Fontes, 2016) or before hilling (Mohr and Tomasiewicz, 2012;Silva and Fontes 2016), even under adequate water conditions.…”
Section: Fresh Tuber Qualitymentioning
confidence: 69%
See 4 more Smart Citations
“…3). The absence of an effect of different K fertilizer application timings (preplanting and prehilling) on the specific gravity of tubers has also been reported in the literature (Kumar et al, 2007, Mohr andTomasiewicz, 2012;Noor et al, 2012;Mello et al, 2018). On the other hand, the specific gravity of potato tubers commonly decreases with the application of KCl, either in the planting furrows (Mohr and Tomasiewicz, 2012;Silva and Fontes, 2016) or before hilling (Mohr and Tomasiewicz, 2012;Silva and Fontes 2016), even under adequate water conditions.…”
Section: Fresh Tuber Qualitymentioning
confidence: 69%
“…3b-3d). Conversely, Mello et al (2018) found the maximum potato yield with a rate of 300 kg K 2 O ha -1 in a sandy soil with medium concentration of exchangeable K, while the maximum tuber yield was reached with a rate of 75 kg K 2 O ha -1 in a loamy sand soil with low exchangeable K. In the site-year with low exchangeable K in the soil, the increase in the total tuber yield in response to K fertilization may be related to the increase in the tuber mean weight (Fig. 3b, 3e), which increased 97% (62 g) with the rate of 276 kg K 2 O ha -1 ; in comparison, the increase was only 21% (14 g) at 83 kg K 2 O ha -1 in the site-year with a high soil test K. It was also observed that potato shoots had died at 80 DAE in the control plots of the experiment in the low soil test K because of an intense K remobilization to the tubers, which are stronger sinks (Kolbe and Stephan-Beckmann, 1997).…”
Section: Tuber Yield and K Removalmentioning
confidence: 98%
See 3 more Smart Citations